Lugar de fé e resistência: estudo toponímico em línguas orais e libras dos terreiros do Recôncavo da Bahia - Jesus, Carlos Messias Alves de (2025)
This thesis aims to select, catalog, and classify the toponyms that designate the terreiros of African-based religions located in the Recôncavo region of Bahia, focusing on the analysis of toponymic motivations in both spoken languages and Brazilian Sign Language (Libras). The research adopts a bilingual approach, treating the names of physical spaces the terreiros os topos (places) subject to scientific analysis. The corpus was defined based on data from the National Institute of Historic and Artistic Heritage (IPHAN) and the Secretariat for the Promotion of Racial Equality (SEPROMI), totaling 420 registered terreiros in the region. Of these, 150 were analyzed for having a corresponding sign in Libras. The theoretical- methodological foundation is anchored in studies of Lexicology, Lexicography and Toponymy (Biderman, 1984; 1998; 2001; Dick, 1990; 1992; Seabra, 2004; 2006; Vilela, 1983; Barreiros, 2017), linguistics applied to Libras (Felipe, 2006; Ferreira, 1995; Souza Júnior, 2012; Quadros; Karnopp, 2019; Quadros, 2020; Sousa, 2022; Marins, 2024; Sousa et. al., 2025), religions of African origin (Verger, 1996; Melo, 2012; Santos, 2012), among others. This research expands the lexicon of Libras in the field of Afro-Brazilian studies, promoting visibility for African-based religions and strengthening historical and sociocultural knowledge among both deaf and hearing communities. As an original contribution, four taxonomies of Brazilian Afro-Indigenous Nature were created, which recognize the spiritual and territorial ties of traditional communities, namely: ilêtopônimo (related to the sacred house), ásétopônimo (referring to ritual power), ibátopônimo (linked to sacred objects), and ewétopônimo (associated with sacred leaves).The final product is the website Ilêtopônimo, available at https://toponimia.zerosevenfive.com.br, which systematizes the data and reaffirms a plural, inclusive, and anti-racist approach, contributing to the appreciation and preservation of Brazil’s cultural heritage in its full diversity.